Taking Advantage of Bacterial Adaptation in Order to Optimize Industrial Production of Dry Propionibacterium freudenreichii - Gaucher, Floriane (Microorganisms, 2019)
Propionibacterium freudenreichii is a beneficial bacterium, used both as a probiotic and as a cheese starter. Large-scale production of P. freudenreichii is required to meet growing consumers’ demand. Production, drying and storage must be optimized, in order to guarantee high P. freudenreichii viability within powders. Compared to freeze-drying, spray drying constitutes the most productive and efficient, yet the most stressful process, imposing severe oxidative and thermal constraints. The aim of our study was to provide the tools in order to optimize the industrial production of dry P. freudenreichii. Bacterial adaptation is a well-known protective mechanism and may be used to improve bacterial tolerance towards technological stresses. However, the choice of bacterial adaptation type must consider industrial constraints. In this study, we combined (i) modulation of the growth medium composition, (ii) heat-adaptation, and (iii) osmoadaptation, in order to increase P. freudenreichii tolerance towards technological stresses, including thermal and oxidative constraints, using an experimental design. We further investigated optimal growth and adaptation conditions, by monitoring intracellular compatible solutes accumulation. Glucose addition, coupled to heat-adaptation, triggered accumulation of trehalose and of glycine betaine, which further provided high tolerance towards spray drying and storage. This work opens new perspectives for high quality and fast production of live propionibacteria at the industrial scale.